A Comparative Investigation of Cyclohexyl‐End‐Capped Versus Hexyl‐End‐Capped Small‐Molecule Donors on Small Donor/Polymer Acceptor Junction Solar Cells. Issue 5 (13th March 2018) - Han, Daehee; Kumari, Tanya; Jung, Sungwoo; An, Yujin; Yang, Changduk
Abstract : Replacing hexyl‐end‐side with cyclohexyl‐end‐side groups on dithieno[3, 2‐ b :2 ′, 3 ′ ‐ d ]silole (DTSi) and dithieno[3, 2‐ b :2 ′, 3 ′ ‐ d ]germole (DTGe)‐based cores yields two new small‐molecule donors: DTSi(FBTTh2 Cy)2 and DTGe(FBTTh2 Cy)2 . Together with the hexyl‐end‐capped analogs DTSi(FBTTh2 )2 and DTGe(FBTTh2 )2, the physical properties, morphology, and organic solar cell (OSC) performances with respect to hexyl‐end‐side versus cyclohexyl‐end‐side groups are investigated. The authors observe that the cyclohexyl‐end‐capped molecules show blue‐shifted film absorptions and lower exothermic crystallization temperatures due to less packed backbones compared to the hexyl‐end‐capped molecules. When used as donor materials with poly(( N, N′ ‐bis(2‐octyldodecyl)‐naphthalene‐1, 4, 5, 8‐bis(dicarboximide)‐2, 6‐diyl)‐ alt ‐5, 5 ′ ‐(2, 2 ′ ‐bithiophene)) polymer acceptor, the relatively improved open‐circuit voltage is achieved from OSCs based on the hexyl‐end‐capped molecules as a result of their deeper‐lying highest occupied molecular orbitals. Nevertheless, the induced higher short‐circuit current density and fill factor parameters lead to better power conversion efficiencies in the cyclohexyl‐end‐capped molecule‐based OSCs. This is attributed to the preferential face‐on orientation with a coarsened morphology, as evidenced by a series of blend film morphological studies. The experimental findings confirm that the cyclized‐end groups in small conjugated materials possess a high potential for improving OSCs. Abstract : Two new small‐molecule donors, DTSi(FBTTh2 Cy)2 and DTGe(FBTTh2 Cy)2, were synthesized by replacing hexyl‐end‐side with cyclohexyl‐end‐side groups on dithieno[3, 2‐ b:2′, 3′‐d ]silole (DTSi) and dithieno[3, 2‐b:2′, 3 ′ ‐d]germole (DTGe)‐based cores. The current results indicate that the cyclized‐end groups in small conjugated materials possess a high potential for improving organic solar cells.